Advancing gender-inclusive agriculture: Leveraging geographic information systems (GIS) integration with smart irrigation technologies - Aeman, Hafsa (International Water Management Institute, 2023)
This abstract delves into the pivotal role played by geographic information systems (GIS) in promoting gender inclusion and equity in agriculture through the integration of smart irrigation technologies. By harnessing the power of GIS, in conjunction with the Internet of Things-enabled soil moisture devices, significant opportunities emerge to empower women and foster gender equality in agricultural practices. This project identifies and explores the potential benefits, challenges, and strategies associated with implementing gender-responsive approaches in the context of GIS-integrated smart irrigation systems. Key opportunities encompass enhanced access to critical information, targeted extension services, collective action and knowledge sharing, as well as improved market access and value-chain participation. It will highlight the importance of addressing challenges such as limited technology access and empowerment in agriculture. To overcome these challenges and maximize the potential of GIS and smart irrigation technologies, various strategies are proposed, including the establishment of tailored digital literacy programs, the promotion of gender-transformative policies and institutional frameworks, fostering partnerships between technology providers and grassroots organizations, and investment in capacity-building initiatives to enhance women’s skills and utilization of GIS and IoT devices. By effectively integrating GIS with smart irrigation technologies, the agricultural sector can advance gender inclusion, leading to sustainable agricultural practices.